The difficulties in teaching science learning in a institution of youth and adults in the municipality of Palm of the Indians / As dificuldades no ensino aprendizagem de ciências em uma instituição de jovens e adultos no município de Palmeira dos Índios - Érica da Silva Ramos; Maria Betânia Aquino da Silva (Universidade Estadual de Alagoas, 2017)
The study presents the difficulties encountered in the teaching learning Educational. We sought to analyze how the curriculum is worked, the support of the school community, the differences between regular education and adult education. It also examined the participation of students and their greater difficulties in this mode. Data were obtained from the application of a questionnaire to the teacher and other students for the 6th and 7th period, pointing the problems that are faced in the school context. The teaching material needs to be suitable for this type of education, and teachers need for continuous training targeted to these students